2019
DOI: 10.1101/695411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inoculation with the mycorrhizal fungus Rhizophagus irregularis modulates the relationship between root growth and nutrient content in maize (Zea mays ssp. mays L.)

Abstract: Plant root systems play an essential role in nutrient and water acquisition. In resource-limited soils, modification of root system architecture is an important strategy to optimize plant performance. Most terrestrial plants also form symbiotic associations with arbuscular mycorrhizal fungi to maximize nutrient uptake. In addition to direct delivery of nutrients, arbuscular mycorrhizal fungi benefit the plant host by promoting root growth. Here, we aimed to quantify the impact of arbuscular mycorrhizal symbios… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
(96 reference statements)
2
5
0
Order By: Relevance
“…Similar results were observed with plant growth promoting rhizobacteria [49]. However, AMF inoculation has previously been shown to promote root growth and branching in different plants [50].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were observed with plant growth promoting rhizobacteria [49]. However, AMF inoculation has previously been shown to promote root growth and branching in different plants [50].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were observed with plant growth promoting rhizobacteria [49]. However, AMF inoculation has previously been shown to promote root growth and branching in different plants [50]. In our experiments we used chlorophyll fluorescence imaging analysis in order to reveal the photosynthetic heterogeneity of the entire leaf zone in both inoculated and non-inoculated plants.…”
Section: Discussionsupporting
confidence: 77%
“…In this regard, the high number of spores obtained in the soil resulted in high root colonization of maize plants (61.69% for 2019 and 40.85% for 2020) regardless of inoculation. Previous studies have reported lower values for root colonization in maize, with values less than 56% 47 and minimum of 39.3% 41 and 22.0% 48 . Therefore, the practice of seed inoculation did not increase the shoot dry matter mass of maize plants.…”
Section: Discussionmentioning
confidence: 74%
“…We would hypothesise that typically the balance between direct and mycorrhizal uptake differs spatially across the root system and temporally over the lifetime of the plant, as well as with respect to host genotype. In addition to delivery of nutrients to the arbuscule, AMF secondarily impacts nutrient uptake through enhancement of root growth and modulation of root development (Ramírez-Flores et al ., 2019). As such, AM symbiosis has the capacity to both mask or exaggerate variation in direct nutrient uptake among host genotypes, a further potential contribution to AMF × QTL effects.…”
Section: Discussionmentioning
confidence: 99%
“…AMF can improve the content of some nutrient elements, such as P, by direct transportation through fungal networks (Chiu & Paszkowski, 2019). AMF can also impact host nutrient status indirectly by altering root architecture or as a consequence of alleviating primary deficiencies (Ramírez-Flores et al ., 2019). Indeed, the concentration of a number of elements can be significantly changed in response to AMF inoculation (Hart & Forsythe, 2012; Ramírez-Flores et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%